Experience report from Cognitive-Behavioral Therapy (CBT) (Research, Society and Development, 2020)
This text aims to report the experience of a specific supervised internship II in the Psychology Service-School of a Federal University, based on the foundations of Cognitive-Behavioral Therapy (CBT). The internship took place in the 2019.1 period, from March to June 2019 at the Specialized HIV/Aids Care Service (SAE). This curricular component aimed at promoting the development, based on the historical and philosophical foundations of CBT, of theoretical and technical skills in conducting the psychotherapeutic process and providing opportunities for exchanging experiences between interns and between them and the supervisor. It is concluded that the internship provided the development of learning about professional practice, providing improvement of listening. The results obtained also showed difficulties in the performance of the Psychologist in serving the local community and contrasts in the theoretical-practical training of students. It is expected that the present work can contribute to the formation of future professionals focused on the context of the social reality to which they are inserted, understanding the need for practical disciplines that aim to promote a critical process about their performance.